Linking Altruism and Self-Control to Life Satisfaction: The Mediating Effect of Organızational Citizenship Behavior - Bramadhian, Revias; Putranta, Martinus Parnawa; Pramudianto, Pramudianto (Department of Management, Faculty of Economics and Business, Brawijaya University, 2023)
Cooperatives members as well as its managers’ life satisfaction are important output for its management performance. Cooperative managers, who have personality traits such as altruism and self-control, tend to have more life satisfaction at their working environment. One of the essential principles of cooperative is organizational citizenship behavior, will help the managers to linking altruism and self-control to their life satisfaction. Cooperative managers who have altruism and good self-control tend to have organizational behavior, so they are more willing to help each other, improving their work performance, and solving problems at the workplace together, thus creating a positive working environment. A positive working environment will make people more satisfied with their life. A cross-sectional design was established and 130 cooperatives managers were selected with snowball sampling among 39 cooperatives in Yogyakarta. Quantitative data were collected by questionnaires and analyzed by using PLS-SEM. The results indicated that organizational citizenship behavior has positive effect on life satisfaction. Altruism and self-control both have positive effect on organizational citizenship behavior and organizational citizenship behavior partially mediates the effect of both altruism and self-control on life satisfaction.